PHYLOGENETIC RELATIONSHIPS AMONG SEVERAL NORTH-ASIAN SPECIES OF THE GENUS AQUILEGIA ACCORDING TO VARIOUS MOLECULAR MARKERS - A. S. Erst; O. V. Vaulin (Вавиловский журнал генетики и селекции)
Molecular study of the nucleotide sequence of the rpl32-trnL spacer and the ITS1-ITS2 fragment of rRNA genes in eight species of the genus Aquilegia sampled in Northern Asia has shown that populations of A. borodinii and A. jucunda from various localities are genetically diverse. The results confi rm that A. viridifl ora and A. atropurpurea are genetically distant from other species studied. The relationship degrees among A. aradanica, A. sibirica, and A. synakensis have been determined. The hybrid origin of A. jucunda is proven.